Exploring the Role of Antinuclear Antibody Positivity in the Diagnosis, Treatment, and Health Outcomes of Patients With Rheumatoid Arthritis - Paknikar, Sujaytha S. (ACR Open Rheumatol, 2021)
OBJECTIVE: The objective of this study was to describe differences in the clinical course of patients with rheumatoid arthritis (RA) who are antinuclear antibody (ANA)–positive compared with those who are ANA‐negative. METHODS: This was a retrospective population‐based cohort study of residents in Olmsted County, Minnesota, who first fulfilled 1987 American College of Rheumatology criteria for RA in 2009‐2014. Data were collected on first documentation of joint swelling. Data on rheumatoid factor or anti‐cyclic citrullinated peptide antibody testing and the ANA level were also collected. Comparisons between groups were performed by using χ(2) and rank sum tests. RESULTS: In this cohort, 64% of patients were tested for ANA within ±90 days of RA criteria fulfillment. In the161 patients with ANA testing, 25% were ANA‐positive. Patients who were ANA‐positive were younger, female, and less likely to be current smokers. ANA positivity did not differ between patients with RA who were seropositive and seronegative. In seropositive patients who were ANA‐positive, there was an increased time to fulfillment of RA criteria, increased time to treatment with disease‐modifying antirheumatic drugs (DMARDs), and increased likelihood of being treated with hydroxychloroquine as opposed to methotrexate. Other outcomes, including disease activity and mortality, did not differ significantly between groups. CONCLUSION: In patients with RA, important differences exist between those who are ANA‐positive and ANA‐negative in terms of time to fulfillment of RA criteria and time to DMARD initiation as well as choice of initial pharmacotherapy. These findings could indicate a difference in clinical presentation or perception of patients with RA who are ANA‐positive. Further research is needed to study the long‐term outcomes of patients with RA who are ANA‐positive.